Visual Illusions: An Interesting Tool to Investigate Developmental Dyslexia and Autism Spectrum Disorder - Gori, Simone; Molteni, Massimo; Facoetti, Andrea (Frontiers in Human Neuroscience, 2016)
A visual illusion refers to a percept that is different in some aspect from the physical stimulus. Illusions are a powerful non-invasive tool for understanding the neurobiology of vision, telling us, indirectly, how the brain processes visual stimuli. There are some neurodevelopmental disorders characterized by visual deficits. Surprisingly, just a few studies investigated illusory perception in clinical populations. Our aim is to review the literature supporting a possible role for visual illusions in helping us understand the visual deficits in developmental dyslexia and autism spectrum disorder. Future studies could develop new tools - based on visual illusions - to identify an early risk for neurodevelopmental disorders.